Towards Self-evolving Context-aware Services - Autili, Marco; Di Benedetto, Paolo; Inverardi, Paola; Tamburri, Damien (Electronic Communications of the EASST, 2008)
The introduction of new communication infrastructures such as Beyond 3rd Generation(B3G) and the widespread usage of small computing devices are rapidlychanging the way we use and interact with technology to perform everyday tasks.Ubiquitous networking empowered by B3G networking makes it possible for mobileusers to access networked software services across continuously changing heterogeneousinfrastructures by resource-constrained devices. Heterogeneity and devices'limitedness, create serious problems for the development and dynamic deploymentof mobile applications that are able to run properly on the execution context andconsume services matching with the users' expectations. Furthermore, the everchangingB3G environment calls for applications that self-evolve according to contextchanges. Out of these problems, self-evolving adaptable applications are increasinglyemerging in the software community. In this paper we describe howCHAMELEON, a declarative framework for tailoring adaptable applications, is beingused for tackling adaptation and self-evolution within the IST PLASTIC project.